Influence of frequency of supplementation and protein concentration in supplements on digestion characteristics of beef steers offered wheat straw - J.L. Beaty; R.C. Cochran; B.A. Lintzenich; E.S. Vanzant; J.L. Morrill; Robert T. Brandt; D.E. Johnson (Kansas Agricultural Experiment Station Research Reports, 1993)
Eight ruminally cannulated steers were used to determine digestion characteristics of soybean meal/sorghum grain supplements containing 12%, 20%, 30%, or 39% crude protein (CP) fed either daily (7X) or three times weekly (3X). The basal forage was wheat straw. Weekly supplement intake was the same per week (30.5 lb) for both frequency groups. The effect of feeding supplements differing in protein concentration on wheat straw intake and dry matter digestibility (DMD) did not depend on frequency of supplementation. Increased frequency of supplementation resulted in greater intake of straw, although DMD was slightly depressed. Increasing protein concentration in the supplements was associated with increases in both straw intake and DMD.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Frequency; Protein; Supplementation; Digestion characteristics